2014
DOI: 10.1016/s1473-3099(14)70946-6
|View full text |Cite
|
Sign up to set email alerts
|

HIV, hepatitis B virus, and hepatitis C virus co-infection in patients in the China National Free Antiretroviral Treatment Program, 2010–12: a retrospective observational cohort study

Abstract: Summary Background Hepatitis-related liver diseases are a leading cause of mortality and morbidity among people with HIV/AIDS taking combination antiretroviral therapy. We assessed the effect of hepatitis B virus (HBV) and hepatitis C virus (HCV) co-infection on HIV outcomes in patients in China. Methods We did a nationwide retrospective observational cohort study with data from the China National Free Antiretroviral Treatment Program from 2010–11. Patients older than 18 years starting standard antiretrovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
126
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(144 citation statements)
references
References 45 publications
14
126
4
Order By: Relevance
“…This finding is similar to rate of co-infection of HIV with gonorrhoea from Mumbai (11.7%) and Kenya (17%) [15,21]. Co-infection of HIV with HCV reported from Kolkata (7.35%) is almost similar to present study (10%) [22]; although a lower rate is documented from South India (2.2%) and China (3.3%) [23,24]. Present study did not encounter co-infection of HIV with HBV while studies from other parts of India have reported this co-infection ranging from 9 to 15.19% [22,23].…”
Section: Discussionsupporting
confidence: 89%
“…This finding is similar to rate of co-infection of HIV with gonorrhoea from Mumbai (11.7%) and Kenya (17%) [15,21]. Co-infection of HIV with HCV reported from Kolkata (7.35%) is almost similar to present study (10%) [22]; although a lower rate is documented from South India (2.2%) and China (3.3%) [23,24]. Present study did not encounter co-infection of HIV with HBV while studies from other parts of India have reported this co-infection ranging from 9 to 15.19% [22,23].…”
Section: Discussionsupporting
confidence: 89%
“…[1][2][3] HCV-related liver disease progression is accelerated in HIV + patients compared to HCV mono-infected patients, and liver decompensation and hepatocellular carcinoma (HCC) have emerged as leading causes of morbidity and mortality in many HIV + patient populations. 4,5 Until recently, HCV was an incurable chronic infection for most HIV + patients.…”
Section: H Epatitis C Virus (Hcv) Co-infection Is Common Among Hiv-inmentioning
confidence: 99%
“…All-cause mortality was also higher in HIV-infected patients with HBV and/or HCV coinfection(s) than in those with HIV only, although ART has generally increased life expectancy of HIV-infected patients (13). Nevertheless, little is known about the impact of ART on the development and progression of liver diseases among people living with HIV and AIDS (PLWHA) in China.…”
Section: Introductionmentioning
confidence: 99%